Mispronunciation and Substitution of Mid-high Front and Back Hausa Vowels by Yorùbá Native Speakers - Sale Maikanti; Yap Ngee Thai; Jurgen Martin Burkhardt; Yong Mei Fung; Salina Binti Husain; Olúwadọrọ̀ Jacob Oludare (REiLA, 2021)
The mid short vowels: /e/ and /o/ are among the vowels shared between Hausa and Yorùbá but differ in Hausa mid-high long, front and back vowels: /e:/ and /o:/. The phonemic differences in the two languages have caused learning difficulties among the Yorùbá native speakers to achieve their second language learning desire and competence. Yorùbá-Hausa learners mispronounce certain disyllabic Hausa words due to the substitution of vowels in the first and second syllables. Thus, both lexical and grammatical meanings of the Hausa words are affected. This study examined the production of the 12 Hausa vowels by level 1 and level 3 students who were learning Hausa as a second language to determine if there was a significant difference in how level 1 and level 3 students pronounced the short and long mid-high, front and back Hausa vowels. 88 Yorùbá native speakers were recruited using purposive sampling. Twenty-four different wordlists extracted from Bargery's (1934) Hausa-English dictionary and prepared in carrier phrases were audio-recorded. It was a mixed-method, and the results were discussed within the theoretical framework of Flege and Bohn's (2020) Revised Speech Learning Model and Corder's (1967) 'Error Analysis Model'. The results of the Mann-Whitney U test revealed that participants in level 1 generally performed lower than level 3 participants in the pronunciation of mid-Hausa vowels due to substitutions. Such errors have pedagogical implication in learning Hausa as a second language, and if not addressed accordingly, the standard of Hausa will continue to fall at an undesirable and alarming rate.